MENGGAMBAR SEBAGAI STRATEGI COPING EMOSIONAL DALAM MENGELOLA STRES DI RUTAN KELAS IIB SERANG - Nur Fadhilah Zahrah; Jannah, Eria Miftahul; Syibyanul Muhibbin; Ahmad Fadhil (Jurnal Tawadhu, 2025)
Stress is a common psychological condition experienced by prisoners due to the pressures of the detention environment, such as loss of freedom, separation from family, social stigma, and uncertainty about the future. If left unmanaged, stress can impact mental health, triggering anxiety, depression, and even aggressive behavior. This study aims to explain the importance of stress management in prisoners and analyze the effectiveness of drawing as an emotional coping strategy in the Class IIB Serang Detention Center. The method used was descriptive qualitative through library research, examining the stress and coping theory of Lazarus & Folkman (1984) and the concept of art therapy by Malchiodi (2003; 2004). The results of the study indicate that drawing as a form of art therapy is effective in helping prisoners express pent-up emotions, reducing anxiety, providing a relaxing effect, and strengthening psychological readiness to face life in detention. In conclusion, drawing can be a simple, inexpensive, and beneficial emotional coping strategy in supporting the mental health and rehabilitation process of prisoners.